Health Training Needs at Primary Care Level Health Facilities in Rural Western Uganda - Kawungezi, Peter Chris; Ntaro, Moses; Stone, Geren; Guiles, Daniel A.; Kenney, Jessica; Bwambale, Shem; Matte, Michael; Wesuta, Andrew Christopher; Ayebare, David Santson; Wetyanga, Moses; Baguma, Stephen; Bagenda, Fred; et al. (Open Journal of Preventive Medicine, 2020)
Introduction: Continual education is recognized worldwide as a tool for the professional development of health care practitioners. It is however effective when the training targets the appropriate needs of the target beneficiaries. This study was therefore aimed at identifying priority training needs of Primary Care Level health professionals in rural Western Uganda. Methods: This was a descriptive cross-sectional survey among 35 rural community health facilities represented by their managers in rural Western Uganda. Participants were invited to Mbarara University of Science and Technology and responded to a self-administered questionnaire and also participated in qualitative group discussions guided by Facilitators from the Community Based Education and Research Services unit within the Community Health Department of Mbarara University of Science and Technology. Priority health training needs were determined based on the computed weighted scores. Results: The majority of managers of rural primary care level health facilities were medical officers by the level of training (51.43%) and male by gender (68.57%). Priority health training needs identified were child health and maternal health with total weighted scores of 12.0 and 10.9 respectively. Qualitatively, emerging themes included; leadership and management, and supervisory roles during student field attachments. Conclusion: Priority health training needs at rural Primary Care level health facilities were child health, maternal health, leadership and management, and supervisory skills. There is dire need to train rural primary care level, health professionals. In-service training based on identified needs should be offered by MUST in partnership with regional stakeholders. This is likely to enhance the quality of services provided by rural primary care level health facilities.
Keywords: Health Training Needs; Rural Health; Rural Medical Education; Continuing Medical Education; Continuous Professional Development; Rural Health Professionals; Primary Care